Identifying Predictors of Perceived Claims of Insurance Fraudulance - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
Insurance fraud affects nearly every industry in the world, costing companies and others that pay insurance premiums billions of dollars per year. Insurance fraud can be found in almost any area of business where liability insurance is carried and intended to protect consumers; illegal activity can be detected in almost any field of business where liability insurance is carried and intended to protect consumers. The aim of this study is to study the predictor/s of anti-insurance fraud among non-insurer companies in Vietnam. This study was conducted using a questionnaire that was completed by 51employees who are currently working in the 11 non-life insurance company in Vietnam. It can be concluded that there exists a significant relationship between all the three independent variables which are namely claim procedure as well as business operation management and the dependent variable which is anti fraud procedure.